2019
DOI: 10.1371/journal.pcbi.1006716
|View full text |Cite
|
Sign up to set email alerts
|

State-aware detection of sensory stimuli in the cortex of the awake mouse

Abstract: Cortical responses to sensory inputs vary across repeated presentations of identical stimuli, but how this trial-to-trial variability impacts detection of sensory inputs is not fully understood. Using multi-channel local field potential (LFP) recordings in primary somatosensory cortex (S1) of the awake mouse, we optimized a data-driven cortical state classifier to predict single-trial sensory-evoked responses, based on features of the spontaneous, ongoing LFP recorded across cortical layers. Our findings show … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
30
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 28 publications
(35 citation statements)
references
References 69 publications
0
30
0
Order By: Relevance
“…Desynchronized states are characterized by lower noise correlations, and it has been hypothesized that the resulting improvement in representation of sensory stimuli underlies improved performance in sensory discrimination tasks [ 14 , 15 , 20 ]. However, we did not find a strong correlation between desynchronization and increased behavioral accuracy, or with better decoding of stimuli from cortical activity, which this hypothesis would predict for our task.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Desynchronized states are characterized by lower noise correlations, and it has been hypothesized that the resulting improvement in representation of sensory stimuli underlies improved performance in sensory discrimination tasks [ 14 , 15 , 20 ]. However, we did not find a strong correlation between desynchronization and increased behavioral accuracy, or with better decoding of stimuli from cortical activity, which this hypothesis would predict for our task.…”
Section: Discussionmentioning
confidence: 99%
“…Recordings in primates showed that low-frequency “noise correlations” (signatures of a more synchronized state) decrease with spatially selective attention, specifically in the region of visual cortex representing an attended part of the visual field [ 14 , 15 , 16 ]. Theoretical arguments suggest that correlated low-frequency fluctuations can impair information coding [ 17 , 18 , 19 , 20 ], and recordings in rodents suggest that cortical sensory representations are more reliable in desynchronized states [ 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 ]. This indicates that cortex might desynchronize in a localized manner, with the resulting decreased noise correlations improving representation of attended sensory stimuli.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…To estimate the depth of L4 in S1 and S2 recordings we considered the LFP, CSD and multi-unit (MUA) responses evoked by contralateral whisker stimuli (Sederberg et al 2019). The average LFP response was obtained by down-sampling to 3 kHz and low-pass filtering the raw signal (forward and reverse, 200 Hz cutoff frequency).…”
Section: Methodsmentioning
confidence: 99%
“…We used a precise, computer-controlled galvanometer (Cambridge Technologies) with attached tube to stimulate individual whiskers (Liew et al, 2020;Sederberg et al, 2019;Waiblinger et al, 2018;. The galvanometer was controlled using either a custom Matlab GUI and Simulink Real-Time (Mathworks), or the Real-time eXperiment Interface application (http://rtxi.org/), sampling at 1 kHz.…”
Section: Whisker Stimulationmentioning
confidence: 99%